The green potential of occupations in Switzerland - Michael Lobsiger; Christian Rutzer (Swiss Journal of Economics and Statistics, 2021)
We use a data-driven methodology to quantify the importance of different skills in performing green tasks, aiming to estimate the green potential of occupations in Switzerland. By this we mean the potential of an occupation to be able to perform green tasks on the basis of the skills attributed to it, whereby it is irrelevant whether the occupation already bundles green tasks or not. The results show that occupations with a high green potential are predominantly those with an engineering and technical background. In order to substantiate our green potential measure, we provide evidence of a positive association between demand of employment in occupations with high green potential and an increase in the implicit tax rate on greenhouse gas emissions. The share of employment in occupations with a green potential above a reasonable threshold in the total Swiss labour force is 16.7% (number of persons employed) and 18.8% (full-time equivalents). These employed persons are, on average, younger, more often men, have a higher level of educational attainment and a higher probability of having immigrated than employed persons in occupations with low green potential.
Keywords: J23; J24; Q52; 330; Green potential; Green transition; Labour market